Gender composition of pairs influences joint action effect - Fabbri, Marco; Martoni, Monica; Beracci, Alessia; Tonetti, Lorenzo; Natale, Vincenzo (Frontiers in Psychology, 2023)
Research on joint action has demonstrated that individuals are sensitive to a coactor’s attentional relation to jointly attend stimuli. It has also been suggested that some features are necessary to resolve the discrimination problem (i.e., self-own and other-own actions). In the present study, we aimed to test whether the gender composition of interacting pairs modulated the joint action effect. Same- (female-female or male-male) and mixed- (female-male) gender pairs performed a joint version of flanker tasks in Experiment 1 (90 participants, 50% males), while in Experiment 2 (154 participants, 50% males) Navon tasks were performed. In Experiment 1, a higher joint flanker effect in same-gender pairs than in mixed-gender pairs, and this joint effect was similar to the classical flanker effect reported by males and females in a classical procedure of the task (70 participants, 50% males). In Experiment 2, the same-gender pairs reported a joint Navon effect, which was reversed in mixed-gender pairs. In conclusion, our findings support how the gender composition of interacting pairs plays a role in joint attentional tasks.